FIgurative Language Analysis in The Dancer Novel - Ayulandari Ayulandari; Elysa Hartati (Jadila: Journal of Development and Innovation in Language and Literature Education, 2023)
Language is a means of communication in social life. Knowing the meaning of a language is very important for us. Because without understanding the meaning of language, the real meaning of the speaker/writer for the listener/reader cannot be understood. In linguistics, this is called semantics. Semantics is the study of the meaning of sentences. The statements used may or may not have the actual meaning. Pictures are a language that has no real meaning. In literary works in the form of novels, writers often use images that are difficult for readers to understand. In semantic studies, aspects of meaning also need to be analyzed more deeply. This study analyzes aspects of language and meaning in the novel ( The Dancer ) by Ahmad Tohari translated from Rene T.A. Lysloff. The purpose of this study is to analyze the novel in a linguistic context. Researchers analyzed the data using a qualitative method.